The rule of 3./2. Fight for power - Walters, Eric, 1957- (Square Fish, Farrar Straus Giroux, 2016)
"In a world gone dark, life goes on for Adam and his fortified neighborhood--but the trade-offs made for safety and security are increasingly wrenching and questionable"--Provided by publisher.